Pengembangan Media Pembelajaran Interaktif Animasi Berbasis Petualangan dalam Pembelajaran IPAS Materi Sistem Pencernaan di Kelas V - Firdausi, Rofiqoh; Ittaqi, Ahmad Faizi (Prodi PGMI STAI Al-Akbar Surabaya, 2024)
This research is motivated by students' lack of interest in learning, and students tend to be passive when learning and the minimal use of media in class can cause learning to be less effective. Researchers carried out research using the Borg & Gall development model, through eight stages, namely Potential and Problems, Data Collection, Product Design, Design Validation, Design Revision, Product Trial, Final Product. In collecting data, researchers used the necessary research instruments including: questionnaires, tests and observation sheets. The research results show that the application of Adventure-Based Animation learning media can improve student learning outcomes. In the small group test before using the media the average score obtained by students was 63.3 in the poor category, meanwhile after using the media the average score of the students was in the good category with a score of 83.3. Meanwhile, in the medium group test, the average pretest score was in the poor category with a score of 60, and in the posttest the students' average score was 84 in the good category.